2019
DOI: 10.9734/ijecc/2019/v9i530116
|View full text |Cite
|
Sign up to set email alerts
|

Study of Aerosol Impact on the Solar Potential Available in Burkina Faso, West Africa

Abstract: This paper is an assessment of aerosols impact on solar potential available in Burkina Faso in 2017. Three measurement stations were selected from the North to the South according to the climatic zones, with sites at Dori (14.035°N, 0.034°W) in the North, Ouagadougou (12.20°N, 1.40°W) in the Center and Gaoua (10.29°N, 3.25°W) in the Southwest, respectively. This study is based on in-situ measurements, satellite observations and a tropospheric standard model of the Streamer radiative transfer code of atmospheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Studies show that aerosols affect the Earth's radiation balance [19,20]. Bado and al showed that mixed or intermediate days are the most frequent and are due to a mixture of dust and combustion particles.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that aerosols affect the Earth's radiation balance [19,20]. Bado and al showed that mixed or intermediate days are the most frequent and are due to a mixture of dust and combustion particles.…”
Section: Discussionmentioning
confidence: 99%
“…The global radiation is obtained by the sum of the direct and diffuse flux. Measurements of global, direct, and diffuse DSSF are also available in Niamey from the Atmospheric Radiation Measurement (ARM) station [28] [33]. All components (diffuse, direct-normal, and global) are measured at a 15 min step and made available for scientific research.…”
Section: Presentation Of Instruments and Datamentioning
confidence: 99%